2021
DOI: 10.1021/acs.molpharmaceut.0c00908
|View full text |Cite
|
Sign up to set email alerts
|

How Molecular Mobility, Physical State, and Drug Distribution Influence the Naproxen Release Profile from Different Mesoporous Silica Matrices

Abstract: Aiming to evaluate how the release profile of naproxen (nap) is influenced by its physical state, molecular mobility, and distribution in the host, this pharmaceutical drug was loaded in three different mesoporous silicas differing in their architecture and surface composition. Unmodified and partially silylated MCM-41 matrices, respectively MCM-41 and MCM-41sil, and a biphenylene-bridged periodic mesoporous organic matrix, PMOBph, were synthetized and used as drug carriers, having comparable pore sizes (∼3 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…12 The release of naproxen from the unmodified and silylated MCM-41 matrix agreed well with its molecular mobility, as probed by the dielectric relaxation spectroscopy. 12 paramount significance to study the molecular dynamics of encapsulated APIs and their effect on the physical properties.…”
Section: ■ Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…12 The release of naproxen from the unmodified and silylated MCM-41 matrix agreed well with its molecular mobility, as probed by the dielectric relaxation spectroscopy. 12 paramount significance to study the molecular dynamics of encapsulated APIs and their effect on the physical properties.…”
Section: ■ Introductionmentioning
confidence: 56%
“…The 13 C and 1 H NMR spectra revealed that the order of SA mobility in the complexes is MC form ≫ HC form > TC form, which coincided with the order of its sublimation. Mobility of a guest compound encapsulated in a host structure such as CD or mesoporous silica can be affected by factors such as cavity size or pore diameter, pore matrix, host/guest interactions, and so on. Generally, an increase in the cavity or pore size of the host compound has a direct effect on the molecular mobility of the guest compound . However, the mobility of SA could not be correlated to the host intermolecular space size, which is in the order of TC form > MC form ≥ HC form.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, SIM-MCM-41 interactions were thoroughly investigated by ATR-FTIR, and the way it is distributed in the matrix was inferred by DSC and molecular dynamics (MD) simulations. MD provided a picture of SIM distribution and anchoring inside pores, which, together with the molecular mobility of the loaded drug, are critical factors that could perform a role in the release mechanism [ 40 ]. The dynamical behavior of loaded SIM was probed by dielectric relaxation spectroscopy (DRS) that monitors reorientational motions of permanent dipoles under the influence of an external oscillating electrical field [ 41 ].…”
Section: Introductionmentioning
confidence: 99%